Evaluating ecological health in the middle-lower reaches of the Hanjiang River with cascade reservoirs using the Planktonic index of biotic integrity (P-IBI). (July 2020) - Zhang, Yingying; Ban, Xuan; Li, Enhua; Wang, Zhi; Xiao, Fei
Graphical abstract: Highlights: Evaluating riverine ecological health in a cascade reservoirs area by P-IBI (phytoplankton and zooplankton). The candidate metrics of Phytoplankton and Zooplankton were established respectively. Water quality and land use and land cover were used to define reference and impaired sites. The ecosystem during the wet season was in better health than that in the dry season, and generally, the aquatic ecological condition in the middle-lower reaches of Hanjiang River was fair. Abstract: Operation of the middle route of the South-to-North Water Diversion Project in the Hanjiang River, China, has made the environmental health downstream of the Danjiangkou Reservoir an important issue for people living along the river. This study used the Planktonic Index of Biotic Integrity (P-IBI) including phytoplankton and zooplankton to evaluate riverine ecological health in an area with cascade reservoirs. Plankton and water samples from 19 sampling sites were collected along the middle-lower reaches of the Hanjiang River in Nov. 2017 and July 2018. To further verify the reliability of the P-IBI results, they were compared with the Saprobic Index (SI) and Comprehensive Water Quality Identification Index (CWQII). Redundancy analysis (RDA) was used to evaluate correlations and variability between P-IBI, SI, CWQII, candidate metrics, and primary environmental factors in the dry and wet seasons. The results showed that the ecological health of the aquatic ecosystem was 'fair' in status, oligotrophic, and class II (wet season)-class III (dry season) as evaluated by the IBI, SI, and CWQII, respectively. The ecosystem during the wet season was in better health than that in the dry season: based on CWQII, water quality at 63% of sites was in class III during the dry season, while 79% of sites were in class II in the wet season; and 11% more sites had IBI-A values (the mean values of Phyto-IBI and Z-IBI) less than 3 IBI scores (indicating "fair" status) in the dry season compared to the wet season. Ecological conditions were also poorer in the reservoir backwater area. The main driving forces impacting aquatic ecosystem in the study area were pollutant emissions and dam impacts. This study demonstrated that the P-IBI is a potential tool for evaluating riverine ecological health in areas with cascade reservoirs.